ANALISIS PROFITABILITAS DAN STRUKTUR MODAL UNTUK MENGUKUR NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN BUMN DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Agis Zaskya; Kalsey Destianola MS; Adam; Muhammad Haekal Yunus; Muh. Zadly Syahdi (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2026)
This study examines profitability and capital structure in measuring firm value in state-owned banking companies listed on the Indonesia Stock Exchange. Firm value reflects investor perception of company performance and is commonly linked to stock price movement in the capital market. This research applies a quantitative method with a descriptive approach, using financial ratio analysis to process the data and facts obtained. The population covers all state-owned banks listed on the Indonesia Stock Exchange, and a purposive sampling technique produced a sample of PT Bank Rakyat Indonesia (BBRI), PT Bank Mandiri (BMRI), PT Bank Negara Indonesia (BBNI), and PT Bank Tabungan Negara (BBTN), observed over five years (2020–2024), resulting in 20 panel data units. Data were collected through documentation of published annual financial reports and analyzed descriptively using profitability ratios (Return on Assets and Return on Equity), capital structure ratios (Debt to Equity Ratio and Capital Adequacy Ratio), and firm value ratios (Price to Book Value and Tobin's Q). The results show that profitability tends to move in line with firm value, where the banks with the highest profitability, BBRI and BMRI, also recorded the highest firm value. Capital structure, measured by the Debt to Equity Ratio, is generally very high as an inherent characteristic of the banking industry, but a strong Capital Adequacy Ratio indicates that the capital structure of the four banks remains well maintained. Profitability and capital structure can therefore be used as benchmarks for measuring and improving the firm value of state-owned banking companies.